The complex interplay between psychological factors and sports performance: A systematic review and meta-analysis - Mert Ayranci; Mehmet Kemal Aydin (PLoS ONE, 2025)
The increasing body of research underscores that athletic performance is not solely contingent upon physical capabilities but is also significantly influenced by psychological strengths. Despite this, there remains a need for comprehensive meta-analyses to rigorously investigate the link between psychological factors and sports performance. In line with this, the present study seeks to examine the influence of various psychological constructs, such as motivation, self-efficacy, self-confidence, goal setting, attention, stress management, extraversion, self-discipline, personality traits, and emotional intelligence (EI) on athletic performance. This analysis was conducted in accordance with PRISMA guidelines and included 127 studies covering a total of 24,358 participants. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, ensuring a rigorous evaluation of study designs and data reliability. The findings indicate an association between personality traits—such as motivation (d = 0.525), self-efficacy (d = 0.413), conscientiousness (d = 0.316), and extraversion (d = 0.336)—and sports performance. Moreover, the overall association between psychological factors and sports performance was calculated as moderate (d = 0.329). Moderator analyses revealed no significant associations based on variables such as gender, type of sport, or type of athlete. Additionally, no significant associations were found for anxiety, openness to experience, neuroticism, or agreeableness, suggesting that these traits may have more complex or context-dependent relationships with performance. The findings of this meta-analysis indicate that psychological skills training plays a critical role in enhancing athletes’ performance. Future research should delve deeper into studies conducted in specific contexts to better understand the ambivalent relations among these factors.